Exposure to multiple metals in early pregnancy and gestational diabetes mellitus: A prospective cohort study. (February 2020) - Wang, Xiaoyi; Gao, Duan; Zhang, Guofu; Zhang, Xu; Li, Qian; Gao, Qin; Chen, Renjuan; Xu, Shangzhi; Huang, Li; Zhang, Yu; Lin, Lixia; Zhong, Chunrong; et al.
Highlights: A prospective cohort study was used to avoid the potential bias errors. It is the first study to show a positive association between Ni and GDM incidence. BKMR models were used to flexibly model the joint effect of the mixture components. All metals mixed exposure was positively related to the risk of GDM. Metal Sb and Ni displayed significant effects within the overall mixture effect. Abstract: Background: A growing number of epidemiologic studies have estimated associations between type 2 diabetes mellitus and exposure to metals. However, studies on the associations of internal assessments of metal exposure and gestational diabetes mellitus (GDM) are limited in scope and have inconsistent outcomes. Objectives: This investigation aimed to explore the associations between urinary nickel (Ni), arsenic (As), cadmium (Cd), antimony (Sb), cobalt (Co), or vanadium (V) in early pregnancy and the subsequent risk of GDM in Chinese pregnant women. Methods: The study population included 2090 women with singleton pregnancy from the Tongji Maternal and Child Health Cohort (TMCHC). Urine samples were collected before 20 gestational weeks, and an oral glucose tolerance test (OGTT) was conducted at 24–28 gestational weeks to diagnose GDM. The concentrations of urinary metals were measured using inductively coupled plasma mass spectrometry (ICP-MS) and were corrected for urinary creatinine. The associations between the risk of GDM and urinary metals were assessed using Poisson regression with a robust error variance with generalized estimating equations (GEE) models and Bayesian kernel machine regression (BKMR). Results: A total of 241 participants (11.53%) were diagnosed with GDM. Five metals (Ni, As, Sb, Co, and V) were found significantly and positively associated with GDM based on single-metal models. In multiple-metal models, for each unit increase of ln-transformed urinary Ni or Sb, the risk of GDM increased 18% [relative risk (RR):1.18, 95%confidence interval (CI): 1.00, 1.38 or RR: 1.18, 95%CI: 1.00, 1.39, respectively]. The BKMR analysis revealed a statistically significant and positive joint effect of the six metals on the risk of GDM, when the urinary levels of the six metals were all above the 55th percentile, compared to the median levels. The effect of metal Ni was significant when the concentrations of the other metals were all fixed at their 25th percentile, and metal Sb displayed a significant and positive effect when all the other metals were fixed at 25th, 50th, and 75th percentiles. Conclusions: To the best of our knowledge, this study is the first to demonstrate that increased concentrations of urinary Ni in early pregnancy are associated with an elevated risk of GDM, either evaluated individually or as a metal mixture. All six metals mixed exposure was positively associated with the risk of GDM, while Sb and Ni were demonstrated more important effects than the other four metals in the mixture.